ANALISIS PENGARUH PROFITABILITAS, UKURAN PERUSAHAAN, LAJU PERTUMBUHAN, DAN KOMPLEKSITAS TRANSAKSI TERHADAP KELEMAHAN PENGENDALIAN INTERNAL - Swastia Nirmala; Daljono Daljono (Diponegoro Journal of Accounting, 2013)
The aim of this research is to analyze the effect of profitability, growth rate, firm size,complexity of the transactions, and internal control weakness State-Owned Enterprises listed in theexamination report of State Audit Agency during the years of 2008 and 2009.There are five variables in this research that consist of four independent variables namelyprofitability, firm size, growth and complexity of the transactions and one dependent variable thatis internal control weakness. There are four hypothesis used in this research that consist ofprofitability negatively affect to internal control weakness, firm size negatively affect to internalcontrol weakness, growth rate positively affect to internal control weakness, and the complexity oftransactions negatively affect to internal control weakness. Statistical method used in this researchis multiple regressions.According to the results of research, it can be concluded that internal control weaknesshave the effect of profitability individually. While firm size, growth rate, and the complexity of thetransactions have the effect of internal control weakness simultaneously.